Thick film resistor paste, thick film resistor, and electronic component
A thick film resistance paste with specific compositions and particle sizes addresses cracking and surge resistance issues in miniaturized electronic components by using silver or palladium powder and lutenium oxide-containing glass, ensuring stable resistance.
Patent Information
- Application Number
- JP2022518161
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-01
- Filing Date
- 2021-04-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-04-30
AI Technical Summary
Thick film resistors in electronic components are prone to cracking due to the use of lutenium oxide-based glass powders, especially in low-resistance applications, and they exhibit negative resistance changes under surge voltage conditions.
A thick film resistance paste comprising silver or palladium powder, lutenium oxide-containing glass powder, and organic binder, with specific ratios and particle sizes, is used to form a sintered body that reduces cracking and enhances surge resistance.
The paste significantly reduces cracking and maintains stable resistance under surge conditions, making it suitable for miniaturized electronic components.
Smart Images

Figure 0007622738000004 
Figure 0007622738000005 
Figure 0007622738000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a thick-film resistor paste, and more specifically, to a thick-film resistor paste that contains a ruthenium oxide-containing glass powder and either or both of a silver powder and a palladium powder, and that is particularly free from cracks in appearance and capable of forming a thick-film resistor that has excellent surge resistance and is used particularly for low resistance, a thick-film resistor that uses the thick-film resistor paste, and an electronic component that includes the thick-film resistor. [Background technology]
[0002] A thick-film resistor paste is generally composed of conductive powder, glass powder, and an organic vehicle for forming them into a paste suitable for printing. This thick-film resistor paste is printed in a desired pattern, and the glass is sintered at a high temperature of usually 800 to 1000°C, to be used as a thick-film resistor that constitutes an electronic component such as a thick-film chip resistor. Ruthenium oxide powder and lead ruthenate powder are widely used as the conductive powder, since the resistance value can be changed gradually by changing the mixing ratio with the glass powder.
[0003] For example, Patent Document 1 discloses a resistor obtained by adding a vehicle using ethyl cellulose as a binder and toluene and alcohol as a solvent to a mixture using mullite as inorganic particles, lead borosilicate glass as glass particles, and ruthenium dioxide as conductive particles. Anti-pe The technology for forming thick film resistors using a paste is described. To achieve a low resistance value of less than 100 Ω, the conductive powder further contains silver or palladium powder, or both.
[0004] Furthermore, Patent Document 2 describes a technology for a thick-film resistor paste in which a composition for a thick-film resistor containing a ruthenium oxide-based conductive powder and a glass frit is further mixed with silver powder and an organic vehicle.
[0005] In recent years, electronic components such as thick-film chip resistors have become smaller, and thick-film resistors are required to have improved electrical properties. In particular, thick-film resistors that are crack-free and have excellent voltage resistance, such as surge resistance, are required. When a momentary high voltage (surge voltage) is applied to a thick-film resistor, it usually shows a negative resistance change, but it is desirable for this resistance change to be small. Such a negative resistance change is thought to be due to the effect of heat generation when a voltage is applied. In conventional thick-film resistor pastes, glass powders are bonded together during sintering, but the softening of the glass powder is limited to the surface layer. Therefore, in the thick-film resistor after sintering the thick-film resistor paste, a dielectric layer equivalent to the glass particle diameter exists. The conductive powder is distributed around this dielectric layer to give the thick-film resistor conductivity. When forming a resistor with low resistance, ruthenium oxide powder is preferably used as the conductive powder, and when a lower resistance is required, silver powder or palladium powder, or a mixture of both, is further contained. Ruthenium oxide is not sinterable, and so cracks tend to occur particularly in low-resistance resistors that contain a large amount of ruthenium oxide.
[0006] Patent Document 3 describes a technology that makes it possible to reduce cracks by further including a polycarboxylic acid-based dispersant in a resistance paste that contains a carbon-based conductive powder and a substituted monohydric phenol resin obtained by a condensation reaction of pt-butylphenol and formaldehyde. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Application Publication No. 4-320003 [Patent Document 2] JP 2019-062178 A [Patent Document 3] Patent No. 4706703 Summary of the Invention [Problem to be solved by the invention]
[0008] However, in recent years, thick-film resistors in electronic components have become smaller and smaller, so there is a demand for thick-film resistor pastes that are heat-resistant at higher temperatures and that are less likely to cause cracks in the resistors even when glass is used as the insulating material. An object of the present invention is to provide a thick-film resistor paste that uses lead borosilicate glass, has no cracks in appearance, and has sufficient surge resistance, and is particularly excellent for low resistance applications; a thick-film resistor using the thick-film resistor paste; and an electronic component equipped with the thick-film resistor. [Means for solving the problem]
[0009] As a result of various studies, the inventors discovered that when a thick-film resistor is formed from a thick-film resistor paste using a ruthenium oxide-containing glass powder having a specific composition, the occurrence rate of cracks is lower than in the past, leading to the invention.
[0010] That is, the thick-film resistor paste according to the present invention contains silver powder or palladium powder, or a mixed powder of both, ruthenium oxide-containing glass powder, and an organic vehicle, and the ruthenium oxide-containing glass powder contains 10 mass % or more and 60 mass % or less of ruthenium oxide, and the glass composition contains silicon oxide with respect to 100 mass % of the glass component. 33 % or more by mass and 60% or less by mass of silicon oxide, 30% or more by mass and 90% or less by mass of lead oxide, and 5% or more by mass and 50% or less by mass of boron oxide, and the total content of silicon oxide, lead oxide, and boron oxide is 50% or more by mass relative to 100% by mass of the glass component.
[0011] In the thick-film resistor paste of the present invention, the ruthenium oxide-containing glass powder preferably has an average particle size of 5 μm or less.
[0012] A thick film resistor according to the present invention is characterized in that it comprises a sintered body of any one of the thick film resistor pastes according to the present invention.
[0013] A low resistance electronic component according to the present invention is characterized by comprising the above-mentioned thick film resistor according to the present invention. Effect of the Invention
[0014] According to the present invention, it is possible to provide a thick-film resistor paste, a thick-film resistor, and an electronic component that can reduce the incidence of cracks on the resistor surface compared to conventional methods and have sufficient surge resistance, and are particularly excellent for low resistance applications. [Brief description of the drawings]
[0015] [Figure 1] 3 is a metallurgical microscope photograph of the surface of the resistor according to Example 1. [Diagram 2] 4 is a metallurgical microscope photograph of the surface of a resistor according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment, and various modifications and substitutions can be made to the following embodiment within the scope of the present invention. The thick-film resistor paste of this embodiment contains silver powder, palladium powder, or a mixture of both, ruthenium oxide-containing glass powder, and an organic vehicle. Each component will be described in detail below.
[0017] (Conductive material) The conductive material in the thick-film resistor paste of the present invention is silver or palladium, or a mixture of both, and ruthenium oxide. A typical thick-film resistor paste has a structure in which a conductive material and glass are each contained in powder form, but the thick-film resistor paste of the present invention does not use ruthenium oxide powder alone as a conductive material, but has a structure in which ruthenium oxide-containing glass powder obtained by pulverizing ruthenium oxide-containing glass produced using ruthenium oxide and glass is used. The particle size of the ruthenium oxide used to form the ruthenium oxide-containing glass powder is not particularly limited, but it is preferable that the specific surface area is less than 5 m2 It is desirable to have a particle size of 5 m / g or more. 2 If the ruthenium oxide content is less than 1000 μm / g, the particle size of the ruthenium oxide will be too large, which may reduce the uniformity of the conductive region in the thick-film resistor and deteriorate the surge resistance. In addition, in the thick-film resistor paste of the present invention, silver powder or palladium powder, or a mixed powder of both, is contained in order to efficiently achieve a low resistance value. The particle size of the silver powder and palladium powder is not particularly limited, but for electronic components that are becoming increasingly smaller, it is desirable to use silver powder with an average particle size of 1 μm to 10 μm, and palladium powder with an average particle size of 0.2 μm to 1 μm. The type of silver powder and palladium powder and the average particle size can be appropriately selected according to the size and characteristics of the resistor to be used.
[0018] (Glass component) The glass component used for the ruthenium oxide-containing glass in the thick-film resistor paste of the present invention contains silicon oxide (SiO2), lead oxide (PbO) and boron oxide (B2O3). In addition, magnesium oxide (MgO), calcium oxide (CaO), barium oxide (BaO), strontium oxide (SrO), cadmium oxide (CdO), tin oxide (SnO), zinc oxide (ZnO), bismuth oxide (Bi2O3), etc. may be contained. Aluminum oxide (Al2O3) may also be contained.
[0019] (Silicon oxide: SiO2) SiO2 is a component that forms the framework of the glass component of the present invention, and its blending amount is 3% by mass or more and 60% by mass or less with respect to 100% by mass of the glass component contained in the ruthenium oxide-containing glass. If it is more than 60% by mass, the softening point of the glass formed will be too high. Also, if it is less than 3% by mass, a chemically stable glass cannot be obtained.
[0020] (Lead oxide: PbO) PbO has the function of lowering the softening point, promoting wetting with ruthenium oxide, and increasing dispersibility. The blending amount is 30% to 90% by mass relative to 100% by mass of the glass component contained in the ruthenium oxide-containing glass. If it is less than 30% by mass, the softening point of the glass formed will be too high. Also, if it is more than 90% by mass, it becomes difficult to obtain a chemically stable glass state.
[0021] (Boron oxide: B2O3) B2O3, together with SiO2, is a component that forms the framework of the glass component of the present invention, and has the effect of lowering the softening point of the glass formed. The blending amount is 5% by mass or more and 50% by mass or less with respect to 100% by mass of the glass component contained in the ruthenium oxide-containing glass. If it is less than 5% by mass, the toughness of the glass formed decreases, cracks tend to occur, and the laser trimming properties deteriorate. If it is more than 50% by mass, phase separation of the glass component tends to occur, and water resistance also decreases.
[0022] (Total content of essential glass components) The total content of SiO2, PbO, and B2O3 is 50% by mass or more relative to 100% by mass of the glass components contained in the ruthenium oxide-containing glass. If the total content is less than 50% by mass, it is difficult to stably form the glass, and it is difficult to obtain satisfactory surge resistance as an electrical characteristic of the thick-film resistor of the present invention.
[0023] (Other glass components) In addition to the above essential glass components, oxides may be further contained as glass components to improve various properties, provided that the properties of the ruthenium oxide-containing glass are not deteriorated. Specifically, Al2O3, MgO, CaO, BaO, SrO, CdO, SnO, ZnO, Bi2O3, etc. may be contained. The blending amount of these glass components is 20 mass% or less for each of 100 mass% of the glass components contained in the ruthenium oxide-containing glass.
[0024] (Ruthenium oxide-containing glass) In the ruthenium oxide-containing glass used in the thick-film resistor paste of the present invention, the mixing ratio of the conductive ruthenium oxide and the glass component is 10% by mass to 60% by mass of ruthenium oxide and 40% by mass to 90% by mass of the glass component, relative to 100% by mass of the ruthenium oxide-containing glass composition. If the ruthenium oxide is less than 10% by mass, the resistance value of the produced ruthenium oxide-containing glass powder becomes too high and it hardly exhibits conductivity. If the ruthenium oxide is more than 60% by mass, the glass component cannot cover the ruthenium oxide powder, and the ruthenium oxide-containing glass becomes brittle. By adjusting the mixing ratio of the ruthenium oxide and the glass component, it is possible to adjust the resistance value of the thick-film resistor to the vicinity of the target resistance value. The ruthenium oxide-containing glass is pulverized to an average particle size of 5 μm or less. If the average particle size is larger than 5 μm, the uniformity of the thick-film resistor decreases, the surge resistance is poor, and there is a risk of cracks occurring on the surface of the thick-film resistor, which is not preferable. The pulverization method can be a ball mill, a planetary mill, a bead mill, etc. In the present invention, the average particle size means the median diameter, and is a value measured by ultrasonically dispersing the powder to be measured in a 2 g / L aqueous solution of sodium hexametaphosphate and using a particle size distribution meter (HPA9320-100X, manufactured by Microtrackbell) using pure water as a solvent.
[0025] (Other additives) The thick-film resistor paste of the present invention may further contain borosilicate glass that does not contain conductive materials and commonly used additives for the purpose of adjusting and improving the resistance value, TCR, and other characteristics of the thick-film resistor. In addition, a dispersant may be contained as an additive to improve dispersibility. Main additives include niobium oxide (Nb2O5), tantalum oxide (Ta2O5), titanium oxide (TiO2), copper oxide (CuO), manganese oxide (MnO2), zirconium oxide (ZrO2), aluminum oxide (Al2O3), etc. The content of the additive can be adjusted according to the desired improved characteristics, but it is preferably 10 mass% or less in the total amount of inorganic substances of 100 mass%.
[0026] (Organic Vehicle) The organic vehicle used in the thick-film resistor paste of the present invention is not particularly limited, and may be one in which a resin such as ethyl cellulose or rosin is dissolved in a solvent such as terpineol, which is used in general resistor pastes. The amount of the organic vehicle may be appropriately adjusted depending on the printing method, etc., but is generally 20% by mass or more and 50% by mass or less with respect to the total amount of the resistor paste, 100% by mass.
[0027] (Method of manufacturing thick film resistor paste) The method for producing a thick-film resistor paste by mixing silver powder or palladium powder, or a mixed powder of both, with a ruthenium oxide-containing glass powder, and an organic vehicle, and further adding lead borosilicate glass powder and additives, etc., as necessary, is not particularly limited, and a general three-roll mill, a bead mill, etc. can be used.
[0028] (Manufacturing method of thick film resistors) The obtained thick-film resistor paste is printed on a ceramic substrate, the organic solvent is removed by drying treatment, and then the substrate is fired at a temperature of, for example, 800° C. to 900° C. to obtain a thick-film resistor. EXAMPLES
[0029] The present invention will be described below in more detail with reference to examples, but the present invention is not limited to these examples.
[0030] Example 1: Evaluation of a resistor with a sheet resistance of 10Ω The glass material was mixed with 60% by mass of ruthenium oxide and 40% by mass of ruthenium oxide, melted, and then cooled to produce ruthenium oxide-containing glass. The glass composition of the conductive glass produced was 100% by mass of glass components, with 33% by mass of SiO2, 48% by mass of PbO, 5% by mass of Al2O3, 7% by mass of B2O3, 2% by mass of ZnO, and 5% by mass of CaO. The obtained ruthenium oxide-containing glass was pulverized in a ball mill to an average particle size of about 1 μm. A thick-film resistor composition containing 28 mass% of ruthenium oxide-containing glass powder, 10 mass% of lead borosilicate glass powder, 32 mass% of palladium-coated silver powder (the mass ratio of palladium to silver is 30:70), 1 mass% of Mn2O3 and 1 mass% of Nb2O5 as additives, and the remainder being an organic vehicle was kneaded in a three-roll mill so that various inorganic materials were dispersed in the organic vehicle, to prepare a thick-film resistor paste of Example 1. The borosilicate lead glass powder contained 33 mass% SiO2, 48 mass% PbO, 5 mass% Al2O3, 7 mass% B2O3, 2 mass% ZnO, and 5 mass% CaO relative to 100 mass% glass components, and the organic vehicle used was 20 mass parts of ethyl cellulose dissolved in 100 mass parts of terpineol. Table 1 shows the composition of the thick film resistor paste of Example 1 and the composition of the ruthenium oxide-containing glass used in producing the thick film resistor paste.
[0031] <Evaluation test> (Preparation of evaluation samples) The thick film resistor paste thus prepared was printed with a width of 1.0 mm between five pairs of electrodes spaced 1.0 mm apart that had been printed on an alumina substrate in advance, and then dried in a belt furnace at a peak temperature of 150°C for 5 minutes. It was then fired in a belt furnace at a peak temperature of 850°C for 9 minutes. Five samples were prepared in the same manner, each for an alumina substrate, to obtain a thick film resistor for evaluation sample 1 (total of 25 pieces). Furthermore, thick-film resistors (5 pieces) of evaluation sample 2 were obtained per alumina substrate in the same manner as evaluation sample 1, except that they were printed with a width of 0.3 mm between electrodes spaced 0.3 mm apart.
[0032] (film thickness measurement) The film thickness was measured by using a stylus-type surface roughness tester to randomly select one alumina substrate from evaluation sample 1, measure the film thickness of each of the five thick-film resistors, and record the average value of the five points as the actual measured film thickness.
[0033] (Converted area resistance value) The resistance values at 25°C of five evaluation samples 1 (total of 25 samples) formed on five alumina substrates were measured using a circuit meter (2001 MULTIMETER, manufactured by KEITHLEY), and the average value was taken as the actual measured resistance value. The converted sheet resistance value when the film thickness was set to 7 μm was calculated using the following formula (1). The calculated converted sheet resistance values are shown in Table 1. 3 As shown in. Converted sheet resistance (Ω) = measured resistance (Ω) × (measured film thickness (μm) / 7 (μm)) (1)
[0034] (Temperature coefficient of resistance: TCR) Five thick-film resistors of evaluation sample 1 formed on one alumina substrate were held in a thermostatic chamber at -55°C, 25°C, and 125°C for 30 minutes, and the resistance values were measured. Each measured resistance value was designated as R -55 , R 25 , R 125 The low-temperature TCR was calculated using the following formula (2), and the high-temperature TCR was calculated using the following formula (3). The average values of the calculated low-temperature TCR and high-temperature TCR for the five points are shown in Table 1. 3 As shown in. Low temperature TCR (ppm / ℃)=[(R -55 -R 25 ) / R 25 ] / (-80)×10 6 (2) High temperature TCR (ppm / ℃)=[(R 125 -R 25 ) / R 25 ] / (100)×10 6 (3)
[0035] (Surge resistance evaluation: resistance change rate) An electrostatic discharge test was carried out on the thick-film resistor of evaluation sample 2 using a semiconductor device electrostatic tester (ESS-6008, manufactured by Noise Laboratory) to apply a voltage under the conditions of a capacitance of 200 pF and an internal resistance of 0 Ω. A voltage of 4 kV was applied to the thick-film resistor of evaluation sample 2 five times at one-second intervals, and the resistance value Rs before and the resistance value Re after the voltage application were measured, and the resistance change rate was calculated using the following formula (4). The average resistance change rate calculated at five points is shown in Table 3. Resistance change rate (%) = (Re-Rs) / Rs × 100 (4)
[0036] (Observation of the surface of a thick film resistor) The surface of the thick-film resistor of evaluation sample 1 was observed using a metallurgical microscope. Appearance where there were only a few microscopic voids due to sintering was rated as "Good", and appearance where there were crack-like defects such as multiple voids connected was rated as "Poor". The evaluation results are shown in Table 3, and a metallurgical microscope photograph of the surface observation is shown in Figure 1.
[0037] (Examples 2 to 12) The glass materials and ruthenium oxide were mixed in the ratios shown in Table 1, melted, and then cooled to prepare ruthenium oxide-containing glasses. The glass composition of each of the prepared conductive glasses was as follows: SiO 2 , PbO, Al 2 O 3 、B 2 O 3 The contents of ZnO and CaO are as shown in Table 1. Each of the obtained ruthenium oxide-containing glasses was pulverized in a ball mill to an average particle size shown in Table 1. A thick-film resistor composition containing ruthenium oxide-containing glass powder, lead borosilicate glass powder, palladium-coated silver powder (mass ratio of palladium to silver: 30:70), additives, and an organic vehicle in the ratios shown in Table 1 was kneaded in a three-roll mill so that the various inorganic materials were dispersed in the organic vehicle, to prepare thick-film resistor pastes of Examples 2 to 12. The lead borosilicate glass powder and the organic vehicle had the same compositions as those used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3. It should be noted that Examples 4, 7, 9, and 10 are reference examples.
[0038] Comparative Example 1 A thick-film resistor paste was prepared by a conventional manufacturing method in which a conductive material and glass were added in powder form without using ruthenium oxide-containing glass. However, if ruthenium oxide powder and glass powder were added without using ruthenium oxide-containing glass powder obtained by crushing ruthenium oxide-containing glass, differences in electrical characteristics (TCR) and the like would occur when adjusting the resistance value to a value suitable for the thick-film resistor paste. Therefore, in Comparative Example 1 prepared by a conventional manufacturing method, in order to adjust the TCR and the like, lead ruthenate powder was mixed in addition to ruthenium oxide powder as a conductive material, and the amounts of ruthenium oxide powder, lead ruthenate powder, palladium-coated silver powder (palladium and silver mass ratio 30:70), and the like were adjusted. That is, the thick-film resistor composition contains 20 mass% ruthenium oxide powder, 5 mass% lead ruthenate powder, 42 mass% palladium-coated silver powder (palladium to silver mass ratio 30:70), 30 mass% glass powder, 1 mass% Mn2O3 and 1 mass% Nb2O5 as additives, and the remainder is an organic vehicle, and is kneaded by a three-roll mill so that various inorganic materials are dispersed in the organic vehicle to prepare a thick-film paste of Comparative Example 1. The glass composition in the prepared thick-film resistor paste is 33 mass% SiO2, 47 mass% PbO, 5 mass% Al2O3, 7 mass% B2O3, 3 mass% ZnO, and 5 mass% CaO relative to 100 mass% of the glass component. The organic vehicle has the same composition as that used in Example 1. The composition of the thick-film resistor paste of Comparative Example 1 and the composition of the glass used in the manufacture of the thick-film resistor paste are shown in Table 2. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 3, and a metallurgical microscope photograph of the surface observation is shown in FIG.
[0039] (Comparative Examples 2 to 10) Ruthenium oxide-containing glasses were produced by mixing and melting the glass materials and ruthenium oxide in the proportions shown in Table 1, and then cooling. The glass composition of each conductive glass produced has the content of SiO2, PbO, Al2O3, B2O3, ZnO, and CaO in the proportions shown in Table 1 relative to 100 mass% of the glass component. Each of the obtained ruthenium oxide-containing glasses was pulverized in a ball mill to an average particle size shown in Table 1. A thick-film resistor composition containing ruthenium oxide-containing glass powder, lead borosilicate glass powder, palladium-coated silver powder (mass ratio of palladium to silver: 30:70), additives, and an organic vehicle in the ratios shown in Table 1 was kneaded in a three-roll mill so that the various inorganic materials were dispersed in the organic vehicle, to prepare thick-film resistor pastes of Comparative Examples 2 to 10. The lead borosilicate glass powder and the organic vehicle had the same compositions as those used in Example 1. Further, thick-film resistors as evaluation samples were prepared in the same manner as in Example 1, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0040] [Table 1]
[0041] [Table 2]
[0042] [Table 3] As shown in Table 3, the thick film resistors of Examples 1 to 12 formed using the thick film resistor paste produced using the ruthenium oxide-containing glass powder of the present invention were found to have less cracking on the surface of the thick film resistor, had a smaller rate of change in resistance value before and after the electrostatic discharge test, and were excellent in surge resistance, compared to the thick film resistor of Comparative Example 1 formed using the conventional thick film resistor paste produced without using the ruthenium oxide-containing glass powder. In addition, it was found that the thick-film resistor of Comparative Example 2, which was formed from a thick-film resistor paste obtained using a ruthenium oxide-containing glass having a ruthenium oxide content lower than the range of the present invention, had an excessively high resistance value for the conductive glass powder and exhibited almost no conductivity. Furthermore, the thick-film resistor of Comparative Example 3, which was formed from a thick-film resistor paste obtained using a ruthenium oxide-containing glass in which the content of ruthenium oxide was higher than the range claimed in the present invention, had crack-like defects on the surface. Furthermore, the thick-film resistors of Comparative Examples 4 to 10, which were formed using thick-film resistor pastes obtained using glass components whose contents of silicon oxide, lead oxide, or boron oxide, or whose total contents of these essential glass components were outside the ranges of the present invention, were found to have a higher rate of change in resistance value before and after the electrostatic discharge test and to have inferior surge resistance compared to the thick-film resistors of Examples 1 to 12.
[0043] From the above test results, it is recognized that the thick film resistor formed using the thick film resistor paste of the present invention suppresses the occurrence of cracks and has excellent surge resistance, and therefore can be suitably used in electronic components, which have become increasingly miniaturized in recent years.
Claims
1. The composition comprises a silver powder, a palladium powder, or a mixed powder of both, a ruthenium oxide-containing glass powder, and an organic vehicle; The ruthenium oxide-containing glass powder contains ruthenium oxide in an amount of 10% by mass or more and 60% by mass or less, The glass composition contains 33% by mass or more and 60% by mass or less of silicon oxide, 30% by mass or more and 90% by mass or less of lead oxide, and 5% by mass or more and 50% by mass or less of boron oxide, relative to 100% by mass of the glass component; The total content of silicon oxide, lead oxide, and boron oxide is 50% by mass or more based on 100% by mass of the glass component. A thick film resistor paste characterized by:
2. 2. The thick-film resistor paste according to claim 1, wherein the average particle size of the ruthenium oxide-containing glass powder is 5 [mu]m or less.
3. A thick film resistor comprising a sintered body of the thick film resistor paste according to claim 1 or 2.
4. An electronic component comprising the thick film resistor according to claim 3.
Citation Information
Patent Citations
Resistor
JP1977054195A
Method of manufacturing paste for resistance body
JP1978100496A
Thick film resistor
JP1992320003A
Plate-like ruthenium oxide powder, method for producing the same, and thick film resistor composition using the same
JP2013053030A
Composition for thick film resistor, thick film resistance paste and thick film resistor
JP2019062178A